Copy number genome alterations are associated with treatment response and outcome in relapsed childhood ETV6/RUNX1-positive acute lymphoblastic leukemia - Bokemeyer, A.; Eckert, C.; Meyr, F.; Koerner, G.; von Stackelberg, A.; Ullmann, R.; Turkmen, S.; Henze, G.; Seeger, K. (Haematologica (Roma), 2014)
The clinical heterogeneity among first relapses of childhood ETV6/RUNX1-positive acute lymphoblastic leukemia indicates that further genetic alterations in leukemic cells might affect the course of salvage therapy and be of prognostic relevance. To assess the incidence and prognostic relevance of additional copy number alterations at relapse of the disease, we performed whole genome array comparative genomic hybridization of leukemic cell DNA from 51 patients with first ETV6/RUNX1-positive relapse enrolled in and treated according to the relapse trials ALL-REZ of the Berlin-Frankfurt-Münster Study Group. Within this cohort of patients with relapsed ETV6/RUNX1-positive acute lymphoblastic leukemia, the largest analyzed for genome wide DNA copy number alterations to date, alterations were present in every ETV6/RUNX1-positive relapse and a high proportion of them occurred in recurrent overlapping chromosomal regions. Recurrent losses affected chromosomal regions 12p13, 6q21, 15q15.1, 9p21, 3p21, 5q and 3p14.2, whereas gains occurred in regions 21q22 and 12p. Loss of 12p13 including CDKN1B was associated with a shorter remission duration (P=0.009) and a lower probability of event-free survival (P=0.001). Distribution of X-chromosomal copy number alterations was gender-specific: whole X-chromosome loss occurred exclusively in females, gain of Xq only in males. Loss of the glucocorticoid receptor gene NR3C1 (5q31.3) was associated with a poor response to induction treatment (P=0.003), possibly accounting for the adverse prognosis of some of the ETV6/RUNX1-positive relapses.